Biocarvão como condicionador da fertilidade e da microbiota de solo de cerrado cultivado com soja - Santos, Janne Louize Sousa (2013)
Biochar is a new word to describe fine-grained, highly porous charcoal made from biological material (biomass), high in organic carbon. According to its formation, biochar has reactions with other components of the soil, contributing for the better conditioners physical, chemical and biological soil properties. The aim of this work was to evaluate of different rates of biochar (0, 2, 4, 8 e 16 Mg ha-1) in the long term experiment with soybean (Glycine Max (L) Merril) in Haplustox soil, Savanna Biome. Experimental design was field experiment with randomized blocks, 4 repetitions (blocks) and 5 treatments (charcoal doses: 0, 2, 4, 8 and 16 Mg ha-1), plot design 10 x 4 m. In 2006, charcoal was ground and incorporated in soil at 0-15 cm, when the experiment was installed. Soil samples were collected during February of 2007 to 2012, at the soybean flowering. Soil fertility, soil microbial biomass and soybean productivity (kg ha-1) were estimated. Diversity of archaeal, bacterial and fungal community were estimated in different rates of biochar, and in biochar before and after amended in soil. Elemental composition of biochar had liming effect on soil fertility; high content of aluminum and pH, did not effect soybean productivity. Soil microbial biomass showed results due to organic matter content in the last year of experimental. Different rates of biocarvão influenced soil microbial diversity. Biocarvão, after conditioning the soil showed microbial diversity similar to soil. Little biochar rates should be tested in soil.